THE ANALYSIS OF FIGURATIVE LANGUAGE (PERSONIFICATION, METAPHOR, SIMILE) IN SELECTED SONNETS BY WILLIAM SHAKESPEARE - Riska Fitriyatul Mar'ati (Universitas Bandar Lampung, 2022)
Figurative language is the use of words, phrases, symbols, and ideas to achieve the desired effect of meaning and is used to give a more beautiful and dramatic impression to every literary work, including this kind of poetry; sonnet. A sonnet is 14-line poetry with one stanza written in iambic pentameter. Sonnets are a type of poetry popularized by William Shakespeare, and he wrote the most famous and essential sonnets in the English language. This study used the qualitative method and content analysis technique. This study focuses on analyzing figurative language in the selected sonnet by William Shakespeare. Based on the study, the results of data analysis show that there are 80 data of figurative language in total, including 27 personifications, 45 metaphors, and 8 similes in six selected sonnets by William Shakespeare. From a pie chart, the percentage of figurative language consists of personification 34%, metaphor 56%, and simile 10%.Based on the table and a pie chart, it was found that metaphor is the most figurative language used in the selected sonnets by William Shakespeare.